Guidelines towards better participation of older adults in software development processes using a new SPIRAL method and participatory approach - Kopeć, Wiesław; Nielek, Radoslaw; Wierzbicki, Adam (Proceedings of the 11th International Workshop on Cooperative and Human Aspects of Software Engineering, 2018)
This paper presents a new method of engaging older participants in the process of application and IT solutions development for older adults for emerging IT and tech startups. A new method called SPIRAL (Support for Participant Involvement in Rapid and Agile software development Labs) is proposed which adds both sustainability and flexibility to the development process with older adults. This method is based on the participatory approach and user empowerment of older adults with the aid of a bootstrapped Living Lab concept and it goes beyond well established user-centered and empathic design. SPIRAL provides strategies for direct involvement of older participants in the software development processes from the very early stage to support the agile approach with rapid prototyping, in particular in new and emerging startup environments with limited capabilities, including time, team and resources.